Development of bismuth alumino borosilicate glass for radiation shielding material. (September 2021) - Sangwaranatee, N.; Cheewasukhanont, W.; Limkitjaroenporn, P.; Borisut, P.; Wongdamnern, N.; Khrongchaiyaphum, F.; Kothan, S.; Kaewkhao, J.
Abstract: The glass specimens in the composition of xBi2 O3 : 20SiO2 : 20ZnO: 5Al2 O3 : (55-x)B2 O3, where x = 10, 15, 20, 25 mol% were investigated the radiation shielding properties. The specimens were melted entirely by using the melt-quenching technique at 1200 ° C. The WinXCom program has been used to compute the mass attenuation coefficient (MAC) in theoretical values. The effective atomic number (Zeff ), the effective electron density (Neff ), and half-value layers (HVL), tenth-value layers (TVL) and buildup factor obtained by calculations were taken into the function of the MAC. The gamma-ray transmission technique was used to measure the MAC in the energy range from 0.223 MeV to 0.662 MeV by using the Compton scattering technique for various energies from the Cs-137 source. The results showed that the experimental values have been agreed with the theoretical values. The density result was found to increase with the increasing of Bi2 O3 concentrations. The MAC, effective atomic number and effective electron density had similar trends increasing when Bi2 O3 concentration increased and decreasing when the energy increased. The HVL & TVL decreased with increasing of Bi2 O3 contents. The HVL & TVL of the specimens were lower than that of the standard shielding materials. The energy absorption buildup factor (EABF) and exposure buildup factor (EAF) also calculate in 0.015–15 MeV. Highlights: xBi2 O3 : 20SiO2 : 20ZnO: 5Al2 O3 : (55-x)B2 O3 were prepared. The high-density radiation shielding glasses were developed. MAC, Zeff, Neff, HVL, TVL, and buildup factor were studied. Shielding properties show better than some standard concretes, and commercial windows.